Revision of the subgenus Aleochara Gravenhorst of the parasitoid rove beetle genus Aleochara Gravenhorst of Japan (Coleoptera: Staphylinidae: Aleocharinae) - Yamamoto, Shûhei; Maruyama, Munetoshi (Zootaxa, 2016)
The Japanese members of the subgenus Aleochara Gravenhorst, 1802 of the genus Aleochara Gravenhorst, 1802 are revised. Six species are recognized: Aleochara (Aleochara) coreana Bernhauer, 1926; A. (A.) curtula (Goeze, 1777); A. (A.) lata Gravenhorst, 1802; A. (A.) parens Sharp, 1874; A. (A.) postica Walker, 1858 [= A. (A.) clavigera Sharp, 1874, n. syn.; A. (A.) nitouensis Bernhauer, 1935, n. syn.; A. (A.) marginicollis Cameron, 1942, n. syn.], and; A. (A.) yaeyamensis n. sp. (Yaeyama Islands, the Ryûkyûs). We recognize A. niponensis Sharp, 1888, sp. rev., currently synonymized under A. clavigera, as a valid species and transfer it to the subgenus Xenochara Mulsant & Rey, 1874. “A. (A.)” kochi Bernhauer, 1941 [=“A. (A.)” globus Pace, 1999, n. syn.] is excluded from Aleochara and re-assigned instead to Paraleochara Cameron, 1920. Paraleochara is new to the Palearctic region, and Paraleochara kochi (Bernhauer, 1941), n. comb. represents the second species of the genus. Lectotypes of A. niponensis, A. parens, and A.discoidea are designated. All species are described, keyed, and figured, with habitus photographs. Line drawings of the adult mouth parts of A. (A.) curtula (Goeze, 1777) are shown. The diversity, distribution, and phylogenetic relationships of the subgenus in Japan are also discussed.